Journal of Sciences, Technology, and Arts Research : A Scholarly Journal (Manila : National University, 2015)
u
u
u
u
Linguist$1 (Bs Assistant Gleaning a Tagalog Lexicon and Grammar from a Small, Lightly Annotated Corpus -- Internationalization at Home (IaH) National University a Potential Hub -- Witchebelles Anata Magcharot kay Mudra na Nagsusuba si Akech Developing a Rule-based Unidirectional Beki Lingo to Filipino Translator -- Accessibility of Deaf Education in the Mainstream Certificate Program of a Private Tertiary Educational Institution in Manila.s
Includes bibliographical references.